Multiple Introductions of Yersinia pestis during Urban Pneumonic Plague Epidemic, Madagascar, 2017 - Voahangy Andrianaivoarimanana; Cyril Savin; Dawn N. Birdsell; Amy J. Vogler; Anne-Sophie Le Guern; Soloandry Rahajandraibe; Sylvie Brémont; Soanandrasana Rahelinirina; Jason W. Sahl; Beza Ramasindrazana; Rado Jean Luc Rakotonanahary; Fanjasoa Rakotomanana; et al. (Emerging Infectious Diseases, 2024)
Pneumonic plague (PP) is characterized by high infection rate, person-to-person transmission, and rapid progression to severe disease. In 2017, a PP epidemic occurred in 2 Madagascar urban areas, Antananarivo and Toamasina. We used epidemiologic data and Yersinia pestis genomic characterization to determine the sources of this epidemic. Human plague emerged independently from environmental reservoirs in rural endemic foci >20 times during August–November 2017. Confirmed cases from 5 emergences, including 4 PP cases, were documented in urban areas. Epidemiologic and genetic analyses of cases associated with the first emergence event to reach urban areas confirmed that transmission started in August; spread to Antananarivo, Toamasina, and other locations; and persisted in Antananarivo until at least mid-November. Two other Y. pestis lineages may have caused persistent PP transmission chains in Antananarivo. Multiple Y. pestis lineages were independently introduced to urban areas from several rural foci via travel of infected persons during the epidemic.